MAPPING POTENTIAL REGION OF THE AGRICULTURAL SECTOR AREA TO INCREASE ECONOMIC DEVELOPMENT IN PENAJAM PASER UTARA REGENCY - Kumalawati, Rosalina; Pratomo, Rahmat Aris; Budiman, Puput Wahyu; Saputra, Erlis; Susanti, Ari; Rijanta, Rijanta; Raharjo, Jany Tri; Danarto, Wisnu Putra; Murliawan, Karnanto Hendra; Yuliarti, Astinana; Muhtar, Ghinia Anastasia; Anggraini, Rizki Nurita (International Conference On Social Science Education, 2023)
Indonesia is an agricultural country and a developing country which has the potential for inequality in development. Inequality in development is increasingly felt in several areas, including Jakarta. As Jakarta becomes more densely populated with increasingly complex problems, there is talk of moving the nation's capital to East Kalimantan Province. North Penajam Paser Regency is one of the locations for moving the new national capital. It is hoped that the relocation can overcome population problems and development inequality. Developmental inequality will continue to occur if it does not receive serious attention. Development inequality can be overcome by paying attention to regional potential, especially in the agricultural sector. Seeing this, it is very necessary to carry out research with the title "Mapping Potential Region of the Agricultural Sector to Increase Economic Development in Penajam Paser Utara Regency". The research was conducted in Penajam Utara Paser Regency using quantitative research methods. The types of data used are primary data and secondary data. Data collection techniques include documentation, observation, interviews, and interview guides, while analysis techniques use Location Quotient (LQ) and Shift Share analysis. The research results show that the agricultural sector's production results are quite varied, from the production of rice, secondary crops, vegetables, and biopharmaceuticals. The highest production result was rice production reaching a total production of 65,534.9 tons over 10 years. Babulu District is the region that produces the largest rice with a total production of 56,688.1 tons over 10 years. Several types of plants have basic commodities so they have the potential to be developed to help improve the community's economy, even though their growth rate is relatively slow. The relatively slow growth rate for each existing commodity means that none of the agricultural sector's commodities are considered superior or mainstay commodities. As we know, the largest average contribution to GRDP comes from the mining and quarrying sector, like other areas in East Kalimantan that are famous for their natural resources, not the agricultural sector.